Stunting Prevention Intervention In Pregnant Women In 2023 - Siti Sri Wahyuni; Maryati Sutarno (CV. Inara, 2024)
Stunting is a disorder of growth and development of children due to chronic malnutrition and repeated infections, which are characterized by their length or height being below standard. Malnutrition-free children are a commitment with the world, including Indonesia. The international world's commitment, contained in the second point of the Sustainable Development Goals, emphasizes the importance of